Gaining perspective on own illness – the lived experiences of a patient education programme for women with treated coeliac disease. Issue 9 (27th January 2016) - Ring Jacobsson, Lisa; Milberg, Anna; Hjelm, Katarina; Friedrichsen, Maria
Abstract : Aims and Objectives: To explore the lived experiences of women with coeliac disease after attending a patient education programme, to gain a broader perspective of its influence. Background: Adults, particularly women, with coeliac disease report suffering from poor well‐being and reduced quality of life in terms of health. Patient education programmes might support and encourage them in the search for possible improvements in lifestyle and in their approach to the disease. Design: A qualitative phenomenological study. Methods: Personal narrative interviews with 14 women suffering from coeliac disease who had participated in an educational programme. Data analysis in accordance with Giorgi was performed. Results: The essential structure of women's lived experiences following their participation in the patient education programme was found to be an interaction with others with the same disease, which left the women feeling individually strengthened. The interaction enabled the participants to acquire a broader view of their life with coeliac disease. As a result, this realigned their sense of self in relation to their own disease. Conclusion: In coping with coeliac disease, it seems that women need interaction with others with the disease to experience togetherness within a group, get the opportunity to compare themselves with others and to exchange knowledge. The interaction appears to result in that women acquire an overview of life with the disease, develop a greater confidence and dare to try new things in life. Relevance to clinical practice: When designing a patient education programme it seems important to consider the needs of persons to meet others with the same disease, and to ask them about their need for knowledge, rather than simply assuming that health care professionals know what they need.